Culture of Seriola dumerili in a marine ecosystem: Insights from genetic and morphometric fish traits and implications of escape events. (5th November 2022) - Šegvić-Bubić, Tanja; Talijančić, Igor; Žužul, Iva; Žuvić, Luka; Grubišić, Leon; Izquierdo-Gomez, David
Abstract: Commercial net-pen mariculture of Seriola dumerili recently started in Mediterranean countries. While the introduction of new species allows for product diversification and strengthens the European seafood market, net-pen farming and escape events can lead to a number of socio-economic and ecological interactions in the coastal zone. To assist in the genetic management of broodstocks and mitigate the effects of escape events, the potential of morphological and genetic traits of wild, farmed and escaped S. dumerili from the Balearic and the Adriatic Sea were examined as a proxy of wild and farmed origin. Body shape, head profile and mouth position allowed correct classification between fish groups (82%). The global F ST of 0.053 across all loci showed significant subdivision between wild and farmed fish, and allowed correct assignment of escapees. Integration of both genetic and morphometric data using the R package assignPOP improved the assignment results of the escaped group with unknown origin. Potential ecological and socioeconomic implications of escape events are discussed, along with guidelines promoting sustainable development of coastal net-pen aquaculture in a future to come. Graphical abstract: Image 1 Highlights: Genetic and morphological differences between wild and farmed S. dumerili exist. The genetic management for the production of S. dumerili fingerlings is poor. Escaped S. dumerili was detected both in landing ports and first selling points. A risk of genetic introgression from farmed S. dumerili over wild populations exists. A knowledge-gap to guarantee the sustainable rearing of S. dumerili was detected.